2018
DOI: 10.1155/2018/6043710
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Inflammatory Mediator, Vasoactive Intestinal Peptide, Modulates the Differentiation and Function of Th Subsets in Rheumatoid Arthritis

Abstract: Genetic background, epigenetic modifications, and environmental factors trigger autoimmune response in rheumatoid arthritis (RA). Several pathogenic infections have been related to the onset of RA and may cause an inadequate immunological tolerance towards critical self-antigens leading to chronic joint inflammation and an imbalance between different T helper (Th) subsets. Vasoactive intestinal peptide (VIP) is a mediator that modulates all the stages comprised between the arrival of pathogens and Th cell diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 108 publications
(152 reference statements)
1
45
0
Order By: Relevance
“…In addition, PGLYRP-1 is a secreted and circulating protein that binds peptidoglycan and promotes inflammation through the activation of innate immune mechanisms (8). A number of studies have demonstrated that an imbalance between the adaptive and innate immune systems driving excessive immune responses is involved in the pathogenesis of RA (9)(10)(11). Furthermore, Fodil et al (12) reported that single nucleotide polymorphisms (SNPs) of Pglyrp1 were associated with RA.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PGLYRP-1 is a secreted and circulating protein that binds peptidoglycan and promotes inflammation through the activation of innate immune mechanisms (8). A number of studies have demonstrated that an imbalance between the adaptive and innate immune systems driving excessive immune responses is involved in the pathogenesis of RA (9)(10)(11). Furthermore, Fodil et al (12) reported that single nucleotide polymorphisms (SNPs) of Pglyrp1 were associated with RA.…”
Section: Introductionmentioning
confidence: 99%
“…Pathogenic infections associated with the onset of rheumatoid arthritis can lead to a faulty immunological tolerance towards essential self-antigens. This can subsequently cause chronic joint inflammation along with an imbalance between the various T helper subsets [7].…”
Section: Rheumatoid Arthritis: Pathogenesismentioning
confidence: 99%
“…The cause of RA remained unclear and was hypothesized to be under the orchestrated regulation of both genetic and epigenetic factors (Villanueva-Romero et al, 2018;Khan et al, 2019). Various genetic biomarkers were detected through genome-wide association studies (Massey et al, 2018;Shadrina et al, 2018;Lopez-Mejias et al, 2019).…”
Section: Introductionmentioning
confidence: 99%